A Comparative Analysis of Selected Synthetic Indicators of Sustainability. (31st May 2016) - Bluszcz, Anna
Abstract: The problem of measuring the level of sustainable development is a current subject of numerous scientific studies. The need to monitor the level of sustainable development results from the strategy of the European Union, the aim of which is the pursuit of equal opportunities for all member countries. The literature review indicates numerous publications on methods and tools for measurement of the level of sustainable development based on quantitative methods, which enable the objectification of the conducted research and conclusions based on them. However, they require having reliable numerical information in all dimensions covered by the study. Multidimensionality of the sustainable development, which concerns the social sphere and the quality of life, the economic sphere and the environmental sphere entails numerous difficulties in the unambiguous, but at the same time its comprehensive measurement. In theory and practice there are many methods and tools concerning this issue, but so far each method has both advantages and disadvantages, therefore there is still no universal tool. Hence the scope of the article, which presents a review of selected synthetic measures used for assessing the level of sustainable development, with special consideration of the levels for Poland and the Czech Republic in the assessed areas of sustainable development. The research methodology can also be used in business practice for assessing the level of the sustainable development of corporations, industrial sectors or regions or cities.